Welcome to this issue of the College's Asia Pacific Journal of Health Management - Neale Fong (ACHSM, 2022)
As I write the registrations for our Annual Asia-Pacific Health Leaders Congress are close to finalising with over 550 health leaders attending on 21-23 September 2023 in Perth, Western Australia. I am sure we are all looking forward to the opportunity to catch up with peers we have not seen for some time and meet new fellows and members of the College. If you have missed this opportunity, put the dates of 11-13 October in your diary as next year we are in Canberra, the capital of Australia.